Poetry & money : a speculation - Robinson, Peter, 1953- (Liverpool University Press, 2020)
Poetry & Money illuminates relationships between poets, poetry, and money from Chaucer to the contemporary times. Through readings of poems variously engaged with money, it proposes ways in which we can come to a fresh understanding of values money may serve to enable, but which are nevertheless beyond price.